2022
DOI: 10.1186/s13287-022-03013-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-induced endothelial cells-derived exosomes accelerate skin flap survival through Lnc NEAT1-mediated promotion of endothelial progenitor cell function

Abstract: Background Flap transplantation is commonly used in reconstructive surgery. A prerequisite for skin flap survival is sufficient blood supply. However, such approaches remain unclear. This study aimed to explore the underlying mechanisms of exosomes derived from human umbilical vascular endothelial cells (HUVECs) exposed to oxidative stress on endothelial progenitor cells (EPCs) and their subsequent influence on the survival of skin flaps. Methods H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…Furthermore, the histological and IHC evaluation revealed significant higher levels of angiogenic and osteogenic markers, increased local infiltration of M2 polarized macrophages in the Exos group, leading to a better repair of rat cranial defect, which corresponded to their strongest ability in vitro. Our results are in parallel with the former conclusion that exosomal NEAT1 could promote angiogenesis [ 15 ]. Moreover, bone regeneration highly depends on angiogenesis, which is a vital step to restore blood flow providing nutrients, further exerting a positive feedback to bone healing [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the histological and IHC evaluation revealed significant higher levels of angiogenic and osteogenic markers, increased local infiltration of M2 polarized macrophages in the Exos group, leading to a better repair of rat cranial defect, which corresponded to their strongest ability in vitro. Our results are in parallel with the former conclusion that exosomal NEAT1 could promote angiogenesis [ 15 ]. Moreover, bone regeneration highly depends on angiogenesis, which is a vital step to restore blood flow providing nutrients, further exerting a positive feedback to bone healing [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies in the past have found that exosomes can effectively participate in the immune response to facilitate tissue regeneration [37,38]. Exosomes from HUVECs were also reported as offering a positive effect in protecting nerve cells from ischemia/reperfusion injury, improving fibroblast photoaging, inducing endothelial progenitor cell homing and inhibiting osteoclast formation to reduce bone resorption [15,[39][40][41]. Particularly, we demonstrated that HUVEC-derived exosomes could directly promote osteogenic differentiation and increase the migratory capacity of BMSCs, and the aforementioned phenomenon was slightly inhibited with the knockdown of NEAT1 (Additional file 3: Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes that are secreted by the above-mentioned cells also have similar functions to cells. Furthermore, lncRNA NEAT1 in exosomes shows overexpression stimulated by oxidative stress on EPC cells, which is the effective therapeutic ingredient of exosomes ( Figure 3C ) ( 51 ). Evidence suggested that ROS concentration in macrophages could be modulated by lncRNA Lethe and lncRNA NTF3-5.…”
Section: Exosomesmentioning
confidence: 99%
“…(B) HOTAIR-MSC EVs improve wound healing in db/db mice via increasing angiogenesis [Adapted from Born et al, doi: 10.1002/adhm.202002070, ( 50 )]. (C) Schematic illustration of the function and mechanisms of HUVEC-Exos on EPCs [Adapted from Guo et al, doi: 10.1186/s13287-022-03013-9, ( 51 )]. *p < 0.05.…”
Section: Exosomesmentioning
confidence: 99%